Formation and Disruption of W-Phase in High-Entropy Alloys - Nicholas Lavery (Metals, 2016)
High-entropy alloys (HEAs) are single-phase systems prepared from equimolar or near-equimolar concentrations of at least five principal elements. The combination of high mixing entropy, severe lattice distortion, sluggish diffusion and cocktail effect favours the formation of simple phases—usually a bcc or fcc matrix with minor inclusions of ordered binary intermetallics. HEAs have been proposed for applications in which high temperature stability (including mechanical and chemical stability under high temperature and high mechanical impact) is required. On the other hand, the major challenge to overcome for HEAs to become commercially attractive is the achievement of lightweight alloys of extreme hardness and low brittleness. The multicomponent AlCrCuScTi alloy was prepared and characterized using powder X-ray diffraction (PXRD), scanning-electron microscope (SEM) and atomic-force microscope equipped with scanning Kelvin probe (AFM/SKP) techniques. Results show that the formation of complex multicomponent ternary intermetallic compounds upon heating plays a key role in phase evolution. The formation and degradation of W-phase, Al2Cu3Sc, in the AlCrCuScTi alloy plays a crucial role in its properties and stability. Analysis of as-melted and annealed alloy suggests that the W-phase is favoured kinetically, but thermodynamically unstable. The disruption of the W-phase in the alloy matrix has a positive effect on hardness (890 HV), density (4.83 g·cm−3) and crack propagation. The hardness/density ratio obtained for this alloy shows a record value in comparison with ordinary heavy refractory HEAs.